Physico-chemical characterization of fruit's castanheira of Brazil - Bouvie, Luana; Borella, Daniela Roberta; Oliveira Porto, Paula Amanda de; Silva, Andrea Carvalho da [UNESP]; Leonel, Sarita [UNESP] (Univ Federal Mato Grosso, 2016)
Bertholletia excelsa's fruit and seed were physic-chemically characterized. At north of Mato Grosso, Brazil, fallen fruits were collected, processed and classified in: Young Mesocarp (MJ); Old Mesocarp (MV); Young Seed (SJ); Old Seed (SV); Almond (A); Floral Remaining (RF); Seed Coat (TS) and Exocarp (EX). Macro and micronutrients were analyzed: Nitrogen (N); Phosphorus (P); Potassium (K); Calcium (Ca); Magnesium (Mg); Sulfur (S); Boron (B); Copper (Cu); Manganese (Mn) and Zinc (Zn). Physical properties were also analyzed: Percentage of Nitrogen and Carbon; C/N ratio; Density; pH and Electrical conductivity. The experimental design was completely randomized with four replication, and each piece of fruit was considered a treatment. The results were submitted to analysis of variance and Tukey test (p > 0.05), for N, P and K was calculated Pearson correlation (95%). Almond concentrate more N, P, Mg, S, and Mn. C/N ratio was lower in seed, in embryo, in exocarp and in floral remaining. High direct correlations are for Nitrogen: SV/EX; SV/TS, for Phosphorus: SV/A; SJ/TS; A/TS; A/SJ and for Potassium: MJ/RF; EX/RF; EX/MJ; SJ/RF; SJ/MF; SJ/EX. High indirect correlations occur for Nitrogen: MJ/RF; EX/MV, for Phosphorus: SJ/A; A/EX and for Potassium: TS/MV. Potassium and Nitrogen are more exported for fruit, Old Mesocarp has a higher C/N rate and the lowest embryo.
Keywords: Stress Wave; Ultrasonic waves; static bending